Pertumbuhan Material Interlayer di Mineral Lempung Smekit di Tanah Leptic Hapludert yang Berkembang di atas Ca-Bentonit di Nanggulan Kulon Progo - Nurcholis, Mohammad; Buntoro, Aris (Universitas Muhammadiyah Surakarta, 2012)
The objective of this study was to understand the mineralogical characteristics of the bentonite and its upper developed soil, at Nanggulan Kulonprogo. Separation and collection of clay fraction were done by fractionation on suspension at pH 10 after organic matter was oxidized using H2O2. Characteristics of clay mineral was analyzed using X-ray diffraction on parallel oriented samples after Mg saturation, glycerol solvation, or K saturation, and its following successive heating at 100Â°C, 300Â°C and 550Â°C. Cation exchange capacity (CEC) and the exchangeable bases were analyzed using saturation of NH4OAc 1N pH 7. Results showed that clay materials of both samples were Ca-bentonite. Comparing with clay from soil, bentonite had peak intensity of the semctite minerals and low value of CEC and exchangeable Ca. Potassium saturation caused incompletely shrinkage of the studied smectite minerals, and it was reflected by a broader peaks at 13,11 Ã . The presence of these broader peaks was interpreted as a growth of interlayer materials that it may alter to smectite-chlorite intergrade minerals.